Enhanced natural antioxidant compounds in red palm olein-based shortening developed for sandwich cookie cream - Mohamad Shah, Nur Khalishah; Sanny, M.; Ab Karim, N. A.; Kuppan, K.; Mat Yusoff, M. (Rynnye Lyan Resources, 2022)
Red palm olein (RPOL) is a premium palm-based product which is underutilized in the local market due to the lack of consumers’ awareness of its nutritional benefits. It was blended with palm oil (PO) and palm stearin (PS) at different ratios 0:50:50, 5:45:50, and 10:40:50 of RPO:PO:PS. These fat blends were developed to produce shortenings with improved antioxidant compounds meant for sandwich cookies cream (SCC). The RPOL exhibited greater liquid-like properties which contributed to softer shortenings yet with significant solid fat content at 25°C (33.58-34.71%) and 37°C (10.25-10.84%), besides similar in melting point (47.80-47.93°C) with the shortening without RPOL (47.93±0.12° C). As the RPOL increased from 0%, 5%, and 10% (w/w), a significant (p<0.05) increase took place in the shortenings’ carotene (18.47±0.42 ppm, 50.32±7.94 ppm, 84.75±1.22 ppm, respectively) and tocopherol (142.67±2.08 ppm, 140.33±1.53 ppm, 150.33±3.06 ppm, respectively) content. Shortening with 5% (w/w) RPOL exhibited a greater ß’ polymorphic form than that of 10% (w/w) RPOL which contributed to its better creaming performance for a sandwich cookie cream.